PENGARUH POLA ASUH ORANG TUA DAN KONFORMITAS TEMAN SEBAYA TERHADAP PERILAKU SEKSUAL PADA REMAJA DI DESA BANGUN REJO KECAMATAN TANJUNG MORAWA KABUPATEN DELI SERDANG TAHUN 2014 - Dwi Putri Armiyati; Asfriyati .; Abdul Jalil Amri Arma (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
AbstractBased on BkkbN (2013) data, adolescents aged 10-19 years old that had done sexual activity before merried 46,18%. According to researcher there were some factors that effected by sexual behavior to the adolescene, there were parenting pattern and peer group conformityThe purpose of research was to know the effect of parenting pattern and peer group conformity on adolescents’s sexual behavior in Bangun Rejo village. The type of this research was analitic survey by using cross sectional method. The population of the research were all aged 13-19 years old and lived together with their parents. The sampling of the research were 114 teenagers that had taken by using purposive sampling technique, with criteria they were adolescents that ever angaged.The results of research by using regression logistic test that shown that there were any significant effect sexual behavior in adolescents in Bangun Rejo village, they were authoritarian mothers (p=0,0001), mothers permissive (p=0,0001) and peer group conformity (p=0,041). Probability prediction with predictor 1 (bad), that was adolescents with authoritarian mothers or permissive and getting strong peer group conformity possibility to had been sexual behavior as much as 99,8%. While with predictor 0 (good), with authoritative mothers and getting weak peer group possibility sexual behavior as much as 12,26%.The parents was askadolescents to discuss living activities, guide, supervise and directing of the adolescents in choosing the good friends. Explained to adolescents about the risk of the dating beyond. For adolescents give priority to learning, establish a good relationship with parents and having a fixed estabilishment in order to avoid from the behavior of peer group that can lead to negative things as well as follow the positive activities.Key words : Sexual Behavior, Parenting Patterns, Peer Group Conformity